2011
DOI: 10.1016/j.febslet.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of RGS2 in regulation of antioxidant homeostasis in neuronal cells

Abstract: Regulator of G-protein Signaling Protein (RGS)-2 is a modulator of anxiety and dysregulation of oxidative stress is implicated in anxiety. Also, RGS2 expression is reported to be induced by oxidative stress. Thus, if oxidative stress induces RGS2 expression and lack of RGS2 causes anxiety, then mechanisms that link RGS2 and oxidative stress potentially critical to anxiety must be revealed. Our study is the first to suggest role of RGS2 in regulation of enzymes involved in antioxidant defense namely glyoxalase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
1
12
1
Order By: Relevance
“…It is clear that high anxiety (Salim et al 2010a; Salim et al 2010b) corresponds to low GSR1, GLO1 and BDNF while no anxiety (Salim et al 2010a) with high levels of these proteins in these models. In agreement with these findings, our recent publication using a neuronal cell culture model of acute oxidative stress, suggests that GLO1 and GSR1 are transcriptionally up-regulated via Regulator of G-protein Signaling protein (RGS)-2 dependent mechanisms (Salim et al 2011). Sub-chronic oxidative stress in this cell line reduced RGS2, GLO1 and GSR1 mRNA and proteins (unpublished observations).…”
Section: Discussionsupporting
confidence: 67%
“…It is clear that high anxiety (Salim et al 2010a; Salim et al 2010b) corresponds to low GSR1, GLO1 and BDNF while no anxiety (Salim et al 2010a) with high levels of these proteins in these models. In agreement with these findings, our recent publication using a neuronal cell culture model of acute oxidative stress, suggests that GLO1 and GSR1 are transcriptionally up-regulated via Regulator of G-protein Signaling protein (RGS)-2 dependent mechanisms (Salim et al 2011). Sub-chronic oxidative stress in this cell line reduced RGS2, GLO1 and GSR1 mRNA and proteins (unpublished observations).…”
Section: Discussionsupporting
confidence: 67%
“…Animal studies on the other hand have been more informative in clarifying role of oxidative stress in anxiety-like behaviors. Several laboratories including ours have reported that pharmacological induction of oxidative stress causes anxiety-like behaviors in rats and prevention of oxidative stress with antioxidant tempol treatment mitigates anxiety-like behaviors [ 3 5 ]. These interesting studies prompted us to examine whether behavioral outcome of pharmacological induction of oxidative stress can be mimicked in situations where oxidative stress occurs as a consequence of psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…This protein-coding gene is expressed in several tissues such as CNS, heart, vasculature, kidney, immune system, lungs, bone and ovaries [78,79]. Interestingly, oxidative stress conditions increase RGS2 mRNA levels [79,80]; moreover, RGS2 contributes to the regulation of some enzymes involved in antioxidant defense, namely glyoxalase-1 and glutathione reductase-1 [81]. Finally, RGS2 has been shown to be involved in the pathophysiology of gastrointestinal inflammation and visceral pain, mostly regulating T-cell immunity [79,82,83].…”
Section: Discussionmentioning
confidence: 99%